Conscience of Nursing Students: We Need to be Trusted and Appreciated, Not Bullied When Doing Clinical Practice in the Era of Covid-19 - Rosliany, Nia; Puspasari, Jehan; Casman, Casman; Silalahi, Malianti (Alta Dharma Publisher, 2023)
Background: Nursing vocational education is one of the education sectors that has quite felt the impact of the Covid-19 disease outbreak because it is mandatory to practice in hospitals so that they have expertise in applied science. Objective: . This study explores the needs of vocational nursing students in carrying out clinical practice in hospitals during the Covid-19 pandemic. Method: The research design used in this study is a qualitative description approach, the sampling technique is purposive sampling, and the analysis uses thematic analysis. The number of participants in this study was 18. Result: The study's results revealed various obstacles students experienced when carrying out clinical practice as illustrated in four themes, namely patients and families doubting our abilities as students and our capabilities as nurses also challenge students. Conclusion: We need to understand that we are learning, shocked, embarrassed, and scared when the nurse scolds us in front of the patient. Recommendation: Policymakers need to carry out more effective clinical practice in the Covid-19 era by improving students' therapeutic communication skills and paying attention to psychological conditions. Building self-resilience and suitable coping mechanisms in student nurses before going into clinical practice